Too Phat baby & whutthadilly? - Too Phat; EMI (Malaysia).; Positive Tone. (Selangor : EMI (Malaysia), 2000)
Contains two tracks taken from the album Whutthadilly?.
CD 1 : Too Phat Baby / (4:12) -- Whutthadilly / (4:17).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English; Songs, English -- Malaysia